VALIDITAS ISI: TAHAP AWAL PENGEMBANGAN KUESIONER - Hendryadi, Hendryadi (Economic Faculty, Attahiriyah Islamic University, 2017)
This paper aims to identify the content validity techniques in the early stages of developing the questionnaire. Using the literature study, it can be concluded: first, there is no standard technique for accessing the content validity. The researchers can use a qualitative, quantitative, or mix methods. Second, the common qualitative techniques used are through in-depth interviews or FGDs with experts (logical validity) or users (face validity). Third, the common statistical techniques used in testing content validity in the last ten years is the content validity index (CVI) based on the expert agreement level on the item (i-CVI) or S-CVI on the questionnaire as a whole. Other statistical techniques such as Kappa coefficients, ANOVA, and correlation are also commonly used in the initial testing process of the questionnaire. Simulation and case study are discussed in the article. Keywords: content validity, CVI, scale development